IMPLEMENTATION OF BLUETOOTH LOW ENERGY TECHNOLOGY AND TRILATERATION METHOD FOR INDOOR ROUTE SEARCH - Bahri Rizaldi; Doni Setio Pambudi; Taufiqotul Bariyah (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2020)
Currently, route search is made easier by the presence of a Global Positioning System (GPS) technology that can be used by using the Maps application on a smartphone. By using the Maps application, people can find out their current location and can find a route to their desired destination. But the level of GPS accuracy will decrease if the user is in a building or in a closed room. This is caused by the satellite signals being sent that are not able to penetrate thick walls or concrete so that the search for routes using GPS is limited to the search for routes outside the building or outdoors. In this research, Bluetooth Low Energy and trilateration are used to determine the location in a room or building and Dijkstra's algorithm for finding the shortest route to the destination location. The proposed method has a location determination error of 0.728 meters with a distance between the user and the beacon less than 10 meters to get a stable signal.